2018
DOI: 10.3390/molecules23040967
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on Species Authenticity for Herbal Products of Celastrus Orbiculatus and Tripterygum Wilfordii from Markets Using ITS2 Barcoding

Abstract: Herbal material is both a medicine and a commodity. Accurate identification of herbal materials is necessary to ensure the safety and effectiveness of medication. With this work, we initiated an identification method to investigate the species authenticity for herbal products of Celastrus orbiculatus and Tripterygum wilfordii utilizing DNA barcoding technology. An ITS2 (internal transcribed spacer two) barcode database including 59 sequences was successfully established to estimate the reliability of species-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…This is because they were found to contain short sequences (approximately 200–230 bp) [ 13 , 38 , 39 ]. Therefore, ITS2 was identified as a good barcode for the purposes of identification and authentication of herbal medicines used as raw materials, processed materials, and finished products [ 39 , 40 , 41 , 42 ]. Additionally, many research articles have reported the need to integrate trnH-psbA and ITS2 regions for plant species identification [ 43 , 44 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is because they were found to contain short sequences (approximately 200–230 bp) [ 13 , 38 , 39 ]. Therefore, ITS2 was identified as a good barcode for the purposes of identification and authentication of herbal medicines used as raw materials, processed materials, and finished products [ 39 , 40 , 41 , 42 ]. Additionally, many research articles have reported the need to integrate trnH-psbA and ITS2 regions for plant species identification [ 43 , 44 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Han et al investigated 1436 samples representing 295 medicinal species from seven herb markets in China, and found that 1260 samples were successfully identified by ITS2 barcodes, among which approximately 4.2% were adulterants [ 29 ]. The survey of species authenticity for herbal products using DNA barcoding showed that only 62% of the 21 samples labeled as “Nan-she-teng ( Celastrus orbiculatus )” and 31% of the 26 samples labeled as “Lei-gong-teng ( Tripterygium wilfordii )” were genuine [ 30 ]. However, in view of the strict regulation, to avoid inspection authorities, the Ephedra raw materials are often transported and traded by lawbreakers in the forms of powder, crude extract, compound preparations, and other processed products.…”
Section: Discussionmentioning
confidence: 99%
“…This was also used to calculate the concentration of the standards in the plant extracts. The peak areas corresponding to gallic acid and rutin were assigned by comparing their retention times with those of the reference standard [60].…”
Section: Preparation Of L Pumila Leaves and Hmp Extractsmentioning
confidence: 99%